(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigates the transformative potential of advanced software technologies in bolstering scientific literacy and exposure among post-primary students in Cross River State, Nigeria. Amid global strides in educational technology, Nigerian schools face persistent challenges, including limited access to digital tools and inadequate teacher training. Employing a descriptive survey design, data were gathered through questionnaires from 400 participants (300 students and 100 teachers) across 10 public secondary schools in Calabar. Results indicate that 70% of students lack access to computers, while 75% of teachers report insufficient training in software integration. However, 85% of respondents believe tools like virtual labs and e-learning platforms could enhance scientific understanding. Key barriers include erratic power supply (92%) and poor internet connectivity (68%). The study proposes mobile-based learning and teacher capacity-building as viable solutions. Recommendations include government-led infrastructure upgrades, curriculum reforms to embed technology, and partnerships with tech firms to provide affordable tools. This research illuminates a path toward leveraging software technologies to foster scientific literacy, equipping students for a technology-driven future.